O uso das tecnologias da informação e comunicação pelo professor de geografia na cidade de Campina Grande – PB - Alencar, Alisson Clauber Mendes de (2017)
With the inclusion of technological resources in the school environment, new methodological possibilities arise to conceive the teaching-learning process of educational contents. Therefore, it is necessary a continuous formation, directed to the use of Information and Communication Technologies (ICT) that is not only exhausted in theories, but that transcends the notes contained in the didactic books and establishes relations with the world lived and perceived by the subjects Who are manipulating these tools. For its materialization and structuring, this article had as methodological procedures a bibliographical, documentary and historical survey that approached in a punctual way the insertion of the public educational policies destined to the implementation of technological resources and, consequently, the digital inclusion in the schools, together with notes on The importance of continuing education for the accomplishment of the teaching practice of the high school geography teacher. And last but not least, questionnaires and interviews were applied to Geography teachers who participated in the ProInfo training. This study aims to: 1) analyze the insertion of the National Program of Educational Technology (ProInfo) in public institutions of basic education; 2) to make reflections about the methodological possibilities of use of technological resources by the teachers of Geography of the high school of the state education network of the city of Campina Grande - PB; 3) Evaluate the continuing education provided by the Center for Educational Technology (NTE) and its influence on the teaching practice of the Geography teacher of this city. The undergraduate courses, considered as initial teacher training, superficially address the use of technological resources in the curricular components directed towards this purpose. Whether it is for a baccalaureate training of the teacher trainer, the hourly load of the curricular component (reduced), the lack of technological resources in the Institutions of Higher Education or the impossibility of an effective monitoring in the activities and actions proposed by the teacher trainer to his student. To fill this gap in the initial training of basic education professionals in public higher education institutions, the federal government, in partnerships with states and municipalities, implemented the National Digital Inclusion Program. The concerns that this study comes to promote are about what was prescribed and what is being done from the implementation of this program in the context of education.